THE NATURE OF TERMS SET FORTH IN THE PROVISIONS UNDER ART. 2502 CPP AND THE SANCTION TO BE APPLIED AS A CONSEQUENCE OF THEIR VIOLATION - Mircea-Constantin SINESCU; Adrian Lucian CATRINOIU; Mihaela SIMINA (Challenges of the Knowledge Society)
This article focuses on reviewing the aspects regarding the nature of terms of 6 months, respectively, of 1 year, which were established for checking the legality and judiciousness of the precautionary measure in the criminal trial, by introduction of art. 2502 CPP. Thus, starting from the review of the nature of such terms, in corroboration with reviewing the purpose itself of this new regulation, one may also conclude what was the legislator’s intention with regard to the sanction to be applied when such are violated, a sanction that was not, however, mentioned expressly. Starting also from the judicial practice which is not constant, namely from the non-uniform mode of construction and application of legal provisions, this article intends to clarify, from a theoretical perspective, the nature of terms referred to in art. 2502 CPP, and also the sanction to be applied as a consequence of violating such terms. We will conclude further with the practice of courts of law, in support of our opinion.